How to Promote Workplace Health in order to Work into Old Age: Experiences from Employees in an Industrial Setting. (1st April 2019) - Lydell, Marie; Hildingh, Cathrine; Söderbom, Arne; Ziegert, Kristina
Abstract : Background . Health is important in workplaces. A good organisational climate in a workplace plays a major role in the employees' well-being at work and is also associated with increased productivity. Today, employees are expected to work into older age and it is a challenge for companies to promote health and well-being for this growing group. Purpose . The purpose of this study was to explore how to promote workplace health at present time and for the end of working life in the perspective of employees. Design/Methodology/Approach . The study had an explorative design, and a thematic analysis was chosen. The inclusion criteria were persons 50 years and older, working in the company and planning to continue working into old age. A total of 21 coworkers (14 men) participated in the study. Three focus group interviews were conducted. Findings . The results from the focus group interviews are presented in four themes: handle change in a changeable workplace, take responsibility for health concerns, get confirmation for feeling needed, and support and tolerance adapted for each employee. Practical Implications . Promoting health should be an urgent mission for employees themselves as well as for managers in order to support employees in working into old age. The health promotion must be suitable for each employee and should be designed in such a way as to avoid inequality in workplace health. Originality/Value . There is a need for more health-promoting behaviours, support, and activities for employees in order to work into old age.